Awig-Awig and Legal Awareness of Community: How Does Customary Law Provide Security for Local People and Aliens? - Dewa Ayu Agung Intan Pinatih; Malik Akbar Mulki Rahman (The Indonesian Journal of International Clinical Legal Education, 2020)
Bali is referred to as an area with high obedience and legal awareness by the community, this does not arise solely in other legal rules which have a large penalty, but because of the awig-awig (traditional regulations) made by Desa Desa Pakraman by involving the community , management and chairman to formulate research rules entitled Awig-Awig Influence on Legal Awareness of Pakraman Batuan Kaler Village, Sukawati Subdistrict, Gianyar Regency, aims to find out To find out the existence of awig-awig in regulating the behavior of Balinese people, understanding the influence of Desa Pakraman in law enforcement nationally, and to find out the existence of awig-awig and Desa Desa Pakraman in the Balinese community. The literature review used in this study is the sense of awig-awig and awig-awig Adat Batuan Kaler Village. This research uses a qualitative descriptive approach with direct observation techniques on the object of research and uses literature review (literature review). After data collection the next step is data analysis, which is the breakdown of a subject for its various parts and the study of the part itself. The results of this study are divided into several sub-discussions, starting from the general picture of awig-awig, the influence of Awig-Awig and Desa Desa Pakraman on the Behavior of Balinese society which includes the existence of awig-awig in Batuan Kaler Village and awig-awig function in law enforcement.